Music Performance Policy during Covid-19 Crisis: Expectations Versus Reality - Hidayatullah, Riyan (JASSP, 2021)
This paper examines public discourse on web pages and social media as a form of digital ethnography during the COVID-19 crisis. During the "lockdown" in Indonesia, internet traffic increased, creating new habits for performance music. A total of 657 tweets, YouTube talk shows, and online news pages were analyzed using NVIVO12. The data was taken using 'Ncapture,' 'Word Frequency,' and 'Sociogram Analysis.' Each keyword was analyzed as a representation of a particular musical problem during the pandemic. The goal is to identify differences between government policies and their implementation. Online activities explore a variety of things about music during the pandemic. The conversation continued with the awareness that the musicians would be offering their peers. Collective sentiments were more stressed during the COVID-19 crisis, giving rise to social unity. The theory of cooperation between music workers is a solution that can be implemented